Comunicação científica no contexto da Web 2.0: Considerações sobre o uso de blogs como canais para a difusão de informações científicas - Pando, Daniel Abraão [UNESP] (My University, 2014)
Scientific communication is undergoing great changes, propelled by the appearance of new tools. After a bibliographical review, the impact of the Web 2.0 and its collaboration tools on scientific communication is analysed, with a focus on blogs. It is concluded that logs are being increasingly used for the dissemination of scientific knowledge; so, they deserve careful attention on the part of the Information Science community.
Scientific communication in the context of the Web 2.0: Considerations on the usage of blogs as channels for the dissemination of scientific information
Keywords: Blogs; Scientific communication; Web 2.0